In silico design novel (5-imidazol-2-yl-4-phenylpyrimidin-2-yl)[2-(2-pyridylamino)ethyl]amine derivatives as inhibitors for glycogen synthase kinase 3 based on 3D-QSAR, molecular docking and molecular dynamics simulation. (October 2020) - He, Qingxiu; Han, Chu; Li, Guangping; Guo, Haiqiong; Wang, Yuxuan; Hu, Yong; Lin, Zhihua; Wang, Yuanqiang
Graphical abstract: Highlights: GSK-3 has been proved as an important therapeutic target in type 2 diabetes mellitus and Alzheimer's disease. The constructed 3D-QSAR model had good predictive ability. Based on 3D-QSAR models and contour maps, we designed 10 novel compounds with good potential activity. We explored the binding feature between GSK-3 and inhibitor by molecular docking and MD simulations. Residues Ile62, Val70 and Lys85 located in the active site play a key role for GSK-3 complexed with inhibitors. Abstract: Glycogen Synthase Kinase 3 (GSK-3) is a member of cellular kinase with various functions, such as glucose regulation, cellular differentiation, neuronal function and cell apoptosis. It has been proved as an important therapeutic target in type 2 diabetes mellitus and Alzheimer's disease. To better understand their structure–activity relationships and mechanism of action, an integrated computational study, including three dimensional quantitative structure-activity relationship (3D-QSAR), molecular docking, and molecular dynamics (MD), was performed on 79 (5-Imidazol-2-yl-4-phenylpyrimidin-2-yl)[2-(2-pyridylamino)ethyl]amine GSK-3 inhibitors. In this paper, we constructed 3D-QSAR using comparative molecular field analysis (CoMFA) and comparative molecular similarity index analysis (CoMSIA) method. The results showed that the CoMFA model ( q 2 = 0.743,   r 2  = 0.980) and the CoMSIA model ( q 2  = 0.813,   r 2  = 0.976) had stable and reliable predictive ability. The electrostatic and H-bond donor fields play important roles in the models. The contour maps of the model visually showed the relationship between the activity of compounds and their three-dimensional structure. Molecular docking was used to identify the key amino acid residues at the active site of GSK-3 and explore its binding mode with ligands. Based on 3D-QSAR models, contour maps and the binding feature between GSK-3 and inhibitor, we designed 10 novel compounds with good potential activity and ADME/T profile. Molecular dynamics simulation results validated that Ile62, Val70 and Lys85 located in the active site play a key role for GSK-3 complexed with inhibitors. These results might provide important information for designing GSK-3 inhibitors with high activity.